Normaliser le sauvage : l'expérience française des cueilleurs professionnels - Claire Julliand; Florence Pinton; Raphaële Garreta; Jean-Paul Lescure (EchoGéo)
The growing interest for natural products is revitalising commercial wild plant gatherings worldwide. In metropolitan France, this activity has long been perceived as marginal, whereas more than 10% of plant biodiversity relates today to this "wild" economy. In 2011, gatherers founded the Association Française des professionnels de la Cueillette de plantes sauvages (AFC) to ensure the preservation of plant resources and prevent from pillages that can occur in rural areas.”. This new collective wishes to have the profession recognized in its diversity and to build a harvesting ethic in consultation with the actors of the sectors using natural ingredients and the environmental managers. Collaborations with actors from the research and environmental conservation communities have made it possible to develop a participative and reflective dynamic to support this professionalization process and to develop the modalities of its implementation. Through this scheme, AFC members will test their values, know-how and relationship to the plant. Building on these shared experiences, from the beginning of the association to the FloreS project, we propose to discuss the renewal of commercial wild plant harvesting in metropolitan France.